Агаар дахь радон, түүний задралын бүтээгдэхүүнийг судалсан тухай - Н, Норов; С, Даваа (Scientific transaction of the National University of Mongolia. Physics, 2022)
The simple method for determination of RaA, RaB and RaC in air by alpha counting of air filters was described. Diurnal variation of radon equilinrium equivalent concentration in outdoor air at some city Mongolia is observed.